Serum cholesterol and leptin levels in patients with borderline personality disorder - Atmaca, M; Kuloglu, M; Tezcan, E; Gecici, O; Ustundag, B (Karger, 2002)
The association between low or lowered cholesterol and impulsivity, aggressive behaviours and suicide remains controversial. In the present study, cholesterol and leptin levels of patients with borderline personality disorder in whom impulsivity, aggressive behaviours and suicide attempts are clearly established have been compared with those of healthy controls. The study group consisted of 16 patients with borderline personality disorder and 16 healthy controls. All patients were assessed with the Barratt Impulsivity Scale (BIS), Buss-Durkee Hostility Inventory (BDHI) and Hamilton Depression Rating Scale (HDRS). Fasting serum cholesterol and leptin levels were measured. The mean cholesterol and leptin levels, of the patient group were significantly lower than those of the controls. Likewise, the patients with current suicidal thoughts and a history of suicide attempt had statistically significantly lower cholesterol and leptin levels compared with the patients without those features. There was an inverse correlation between both cholesterol and leptin levels, and impulsivity as determined by the BIS or aggression as determined by the BDHI, but no correlation between both cholesterol and leptin levels and the HDRS was found in the patients. In conclusion, the present study demonstrates that the patients with borderline personality disorder have lower cholesterol and leptin levels than healthy controls. Low serum cholesterol and leptin levels are associated with all dimensions of the disorder - impulsivity, aggression and suicidality but are not associated with the presence and the severity of comorbid depression. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: cholesterol; leptin; suicide; borderline personality disorder; impulsivity